Verification of the presence of capsule gene sequences in nasopharyngeal isolates of nontypeable Haemophilus influenzae from healthy children at a Brazilian day care center - Bonifácio Da Silva, Maria Emilia [UNESP]; Marin, José Moacir (My University, 2001)
Fifty-eight nasopharyngeal isolates of Haemophilus influenzae were collected from healthy children at a day care center, and nontypeable isolates were examined by Southern blot for the presence of capsule gene sequences. Seven isolates (12%) demonstrated homology with capsule-specific sequences. One isolate was characterized as an H. influenzae type b capsule-deficient strain.
Keywords: Cap gene; Day-care center; Haemophilus influenzae